2016
DOI: 10.9745/ghsp-d-16-00236
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Research as Advocacy: The Case of Sayana Press in Kinshasa, Democratic Republic of the Congo

Abstract: The pilot study obtained Ministry of Health approval to allow medical and nursing students to provide the injectable contraceptive Sayana Press and other methods in the community, paving the way for other task-shifting pilots including self-injection of Sayana Press with supervision by the students as well as injection by community health workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…The first pilot in 2015 tested the use of medical/nursing students to administer DMPA-SC (along with pills, condoms, and CycleBeads). 35 , 36 The positive results led to 3 additional pilots in Kinshasa. The first two, conducted in Kinshasa, tested the acceptability and feasibility of using this same cadre of student to provide Implanon NXT and to teach women in the community to self-inject DMPA-SC.…”
Section: Prospects For Improving National Family Planning Coveragementioning
confidence: 99%
“…The first pilot in 2015 tested the use of medical/nursing students to administer DMPA-SC (along with pills, condoms, and CycleBeads). 35 , 36 The positive results led to 3 additional pilots in Kinshasa. The first two, conducted in Kinshasa, tested the acceptability and feasibility of using this same cadre of student to provide Implanon NXT and to teach women in the community to self-inject DMPA-SC.…”
Section: Prospects For Improving National Family Planning Coveragementioning
confidence: 99%
“…A 2015 pilot study in Kinshasa used medical and nursing (M/N) students to deliver DMPA-SC and other methods at the community level. It showed that women were highly satisfied with the method and service received from these providers [15] , [16] . Local Ministry of Health (MOH) officials encouraged further testing of innovative strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other countries where DMPA-SC has been introduced and studied as small pilot projects [15][16][17] , DMPA-SC was introduced in Nigeria in 2015 through multiple channels-facilities, drug shops, and specially-trained community-based distributors-in the private health care sector which accounts for the majority of all health services provided, and in particular for contraceptive services 10 . This presented an opportunity to assess actual user experiences with DMPA-SC from the broader population of new and continuing contraception users under real world conditions.…”
Section: Introductionmentioning
confidence: 99%